Lipid Metabolism and Statin Therapy in Neurodegenerative Diseases: An Endocrine View - Antonella Di Sarno; Fiammetta Romano; Rossana Arianna; Domenico Serpico; Mariarosaria Lavorgna; Silvia Savastano; Annamaria Colao; Carolina Di Somma (Metabolites)
Background/aim: A growing body of evidence suggests a link between dyslipidemias and neurodegenerative diseases, highlighting the crucial role of lipid metabolism in the health of the central nervous system. The aim of our work was to provide an update on this topic, with a focus on clinical practice from an endocrinological point of view. Endocrinologists, being experts in the management of dyslipidemias, can play a key role in the prevention and treatment of neurodegenerative conditions, through precocious and effective lipid profile optimization. Methods: The literature was scanned to identify clinical trials and correlation studies on the association between dyslipidemia, statin therapy, and the following neurodegenerative diseases: Alzheimer’s disease (AD), Parkisons’s disease (PD), Multiple sclerosis (MS), and Amyotrophic lateral sclerosis (ALS). Results: Impaired lipid homeostasis, such as that frequently observed in patients affected by obesity and diabetes, is related to neurodegenerative diseases, such as AD, PD, and other cognitive deficits related to aging. AD and related dementias are now a real priority health problem. In the United States, there are approximately 7 million subjects aged 65 and older living with AD and related dementias, and this number is projected to grow to 12 million in the coming decades. Lipid-lowering therapy with statins is an effective strategy in reducing serum low-density lipoprotein cholesterol to normal range concentrations and, therefore, cardiovascular disease risk; moreover, statins have been reported to have a positive effect on neurodegenerative diseases. Conclusions: Several pieces of research have found inconsistent information following our review. There was no association between statin use and ALS incidence. More positive evidence has emerged regarding statin use and AD/PD. However, further large-scale prospective randomized control trials are required to properly understand this issue.